(3ebOeI aj GdEMUGAs - (3YOfGf(B, (3MShfs ((3YeGf(B:s (3OGQ GdeSjQI ddfTQ hGdJhRjY(B,s, 2002)
(3LeY GdHjGfGJ hYQVgG, ebGjjS GdfRYI GdeQcRjI, ecGjjS GdJTJJ, ebGjjS GdGdJhGA hGdJaQWM, GdYdGeI GdeYjGQjI hGdJhRjY GdWHjYj GdeYjGQj, GdGMJeGdGJ, GdGQJHGW hGdGfMOGQ, GdSdGSd GdRefjI, GdCQbGe GdbjGSjI, GdGMUGA GdMjhjIs
(3GdeQGLY U(B. 319s
Keywords: (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s; (3GdEMUGA GdQjGVjs